Studi Adaptasi Ikan Seluang (Rasbora agryotaenia) Berdasarkan Tahap Domestikasi dari Perairan Sebangau - Tania Serezova Augusta (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
This study aims to determine the adaptation of Seluang fish (Rasbora agryotaenia) based on the domestication stage of Sebangau waters. This research started in January until February 2018. The research method used is a survey and experimental observation. The size of the tarpaulin pond used for domestication is 2 x 3 m, with a water height of 30 cm. The number of fish sampled is 200 heads. Feed is given as much as 5% of the total weight of the fish kept, feeding done twice a day (morning and afternoon). This domestication activity is still not perfect, because only part of the life cycle of fish (Rasbora agryotaenia) can be done in the cultivation system (survival and eating commercial feed). During maintenance activities, the amount of feed used was 63.840 g with the final weight of the fish was 16.905 g. Survival rate (SR) of fish (Rasbora agryotaenia) during maintenance was 73.5% and deaths 26.5%. From the calculation is known that the Feed Conversion Ratio (FCR) for fish (Rasbora agryotaenia) 2.8. This domestication stage starts with the preparation of maintenance pools, fishing in nature, sorting, distribution, and maintenance. During maintenance, five samples of sample fish were taken and five times the pool water quality measurement. From the five weights of the sample fish, it is known that the average weight of the fish is kept, I = 0.003 g, II = 0.042 g, III = 0.051 g, IV = 0.082 g, V = 0.115 g. From the measurement of water quality of tarpaulin ponds, it is known that the mean value of water quality parameters, for DO ranges from 1.5 to 8.8 mg / L, the pH ranges from 5.5 to 7.2 and temperatures range from 27.4 to 27.7 0C.